2003
DOI: 10.1046/j.1432-1033.2003.03488.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Antifreeze’ glycoproteins from polar fish

Abstract: Antifreeze glycoproteins (AFGPs) constitute the major fraction of protein in the blood serum of Antarctic notothenioids and Arctic cod. Each AFGP consists of a varying number of repeating units of (Ala-Ala-Thr) n , with minor sequence variations, and the disaccharide b-D-galactosyl-(1fi3)-a-N-acetyl-D-galactosamine joined as a glycoside to the hydroxyl oxygen of the Thr residues. These compounds allow the fish to survive in subzero ice-laden polar oceans by kinetically depressing the temperature at which ice g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
204
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(209 citation statements)
references
References 120 publications
(157 reference statements)
3
204
0
2
Order By: Relevance
“…[55][56][57] For example, antifreeze glycoproteins (AFGPs) isolated from fish blood plasma consist of a regular tripeptide sequence of Ala-Ala-Thr with a disaccharide fragment (-D-galactosyl-(1-3)--D-galactosamine) linked to the threonine residue. [58][59][60][61] It is noteworthy that the polysaccharide described here displays a structural feature very close to that present in AFGPs. Actually, a -N-acetyl-galactosamine is substituted by an -galacturonosyl residue bearing an amide-linked threonine.…”
Section: Discussionsupporting
confidence: 51%
“…[55][56][57] For example, antifreeze glycoproteins (AFGPs) isolated from fish blood plasma consist of a regular tripeptide sequence of Ala-Ala-Thr with a disaccharide fragment (-D-galactosyl-(1-3)--D-galactosamine) linked to the threonine residue. [58][59][60][61] It is noteworthy that the polysaccharide described here displays a structural feature very close to that present in AFGPs. Actually, a -N-acetyl-galactosamine is substituted by an -galacturonosyl residue bearing an amide-linked threonine.…”
Section: Discussionsupporting
confidence: 51%
“…31,42,44 AFGPs consist of n ¼ 4-50 tripeptide repeats of (Ala-AlaThr) n with the disaccharide galactose-N-acetylgalactosamine attached to each hydroxyl oxygen atom of the Thr residues. 45,46 AFGPs are categorized into eight classes of isoforms with AFGP1 corresponding to the largest glycoproteins (M w ¼ 34 kDa) and AFGP8 to the smallest (M w ¼ 2.6 kDa). 4 No solution structure is available for AFGPs, since they are polydisperse, flexible, and rather disordered.…”
Section: Structure Of Ice-binding Proteinsmentioning
confidence: 99%
“…4 No solution structure is available for AFGPs, since they are polydisperse, flexible, and rather disordered. 46 Fish type I AFPs also have a highly repetitive amino acid sequence. The two type I AFPs from winter flounder, for example, are rich in alanine and have an a-helical fold with 11-residue periodicity [Figs.…”
Section: Structure Of Ice-binding Proteinsmentioning
confidence: 99%
“…Although such proteins were first thought to act via a colligative effect, by decreasing the meting point of water, it was later observed that they act by preventing the growth of ice crystals, having only a small effect on colligative properties [237]. The ability to modify the rate and shape of ice-crystal growth and protect cellular membranes during lipid-phase transitions has resulted in identification of a number of potential applications of AFGPs as food additives, and in applications for the cryopreservation and hypothermal storage of cells and tissues [238,239].…”
Section: Survival In Frozen Environmentsmentioning
confidence: 99%